2020
DOI: 10.21037/atm.2020.02.147
|View full text |Cite
|
Sign up to set email alerts
|

A rapid response team is associated with reduced overall hospital mortality in a Chinese tertiary hospital: a 9-year cohort study

Abstract: Background: Although the evidence for its effectiveness remains uncertainty, rapid response systems are implemented across many hospitals across the world. Increasingly, hospitals in China have recently started to adopt a medical emergency or rapid response team (RRT). Hence, we aimed to determine whether the implementation of an RRT in Chinese hospitals also improved outcomes. Methods: Our hospital is a Joint Commission International (JCI) accredited, tertiary teaching hospital with 1,200 beds. We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…1 for additional details of the screening process. Most studies reviewed fit within two categories: they examined the effects of rapid response implementation on patient outcomes ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Chen et al., 2015 ; Davis et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Mankidy et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ), or they described rapid response systems and their associations with patient characteristics and outcomes ( Jung et al., 2022 ; Winterbottom and Webre, 2021 ; Avis et al., 2016 ; Bunch et al., 2019 ; Chan et al., 2016 ; Churpek et al., 2017 ; Jones et al., 2017 ; Kollef et al., 2017 ; Le Guen et al., 2015 ; Psirides et al., 2016 ; Silva et al., 2016 ; Smith et al., 2015 ; Stelfox et al., 2015 ; Sulistio et al., 2015 ). Generally, rapid response system implementation studies included scenarios in which the system implemented was the first iteration of its kind ( Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ), was replacing an existing system ( Aitken et al., 2015 ), or added another tier of clinical experience or surveillance to an existing system ( Davis et al., 2015 ; Kawaguchi et al., 2015 ; Pirret et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 for additional details of the screening process. Most studies reviewed fit within two categories: they examined the effects of rapid response implementation on patient outcomes ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Chen et al., 2015 ; Davis et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Mankidy et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ), or they described rapid response systems and their associations with patient characteristics and outcomes ( Jung et al., 2022 ; Winterbottom and Webre, 2021 ; Avis et al., 2016 ; Bunch et al., 2019 ; Chan et al., 2016 ; Churpek et al., 2017 ; Jones et al., 2017 ; Kollef et al., 2017 ; Le Guen et al., 2015 ; Psirides et al., 2016 ; Silva et al., 2016 ; Smith et al., 2015 ; Stelfox et al., 2015 ; Sulistio et al., 2015 ). Generally, rapid response system implementation studies included scenarios in which the system implemented was the first iteration of its kind ( Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ), was replacing an existing system ( Aitken et al., 2015 ), or added another tier of clinical experience or surveillance to an existing system ( Davis et al., 2015 ; Kawaguchi et al., 2015 ; Pirret et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Broad patterns of what rapid response system components were reported on in included studies were also assessed. A majority of studies (27 of 34) identified what rapid response system triggers were used ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Chen et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Jung et al., 2022 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ; Bunch et al., 2019 ; Churpek et al., 2017 ; Kollef et al., 2017 ; Le Guen et al., 2015 ; Psirides et al., 2016 ; Silva et al., 2016 ; Smith et al., 2015 ; Stelfox et al., 2015 ; Sulistio et al., 2015 ); additionally, a majority of studies (28 of 34) also included at least some details related to member composition of their medical emergency teams ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Davis et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Jung et al., 2022 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Mankidy et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ; Winterbottom and Webre, 2021 ; Avis et al., 2016 ; Bunch...…”
Section: Resultsmentioning
confidence: 99%
“…In a later study, Santhanam S. (2018) documented an overarching hospital mortality rate with an RR of 0.79, emphasizing a CI spanning 0.63 to 0.98 [ 75 ]. Gong XY (2020) further enriched the literature with evidence accentuating a significant dip in hospital mortality ( p = 0.025) [ 82 ]. Bolstering these narratives, a meticulous systematic review and meta-analysis inferred that the institution of a pediatric rapid response team is invariably tethered to a substantial decrement in hospital mortality, characterized by an RR of 0.88 and a 95% CI of (0.83–0.93) [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated in-hospital mortality after RRT implementation, with estimates ranging from 8% to 15% (Currey et al, 2022;Lyons et al, 2019;Shoaib et al, 2021;Smith et al, 2017). Gong et al (2020) reported that RRT implementation reduced overall in-hospital mortality by 40%; however, two studies (Considine et al, 2017;Padilla & Mayo, 2019) highlighted that delayed RRT activation were strongly associated with a higher rate of in-hospital mortality. Considine et al (2017) reported that patients who received RRT activation within 72 hours of emergency admission were four times more vulnerable and had a 10-fold increase in unexpected in-hospital death.…”
Section: Mortalitymentioning
confidence: 99%